1976
DOI: 10.1080/00365517609055256
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium and Zinc in Human Liver and Kidney

Abstract: Liver and kidney samples obtained from 76 autopsies were analyzed for cadmium and zinc content. The patients had died of various internal diseases. None of them had any known occupational exposure to cadmium. A record was made of age, sex, place of residence, diagnosis, and smoking habits of each patient. The results showed no significant correlation between cadmium accumulation and hypertension or cardiovascular disease. There was, however, a significantly higher kidney cadmium level in smokers than in nonsmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Such a relationship has been reported earlier for MT levels in human renal cortex or liver and metal content [26]. The metal content of the healthy kidney is within the range of results of earlier reports that estimated the Zn and Cd contents in Canadians [26]and Swedes [27]. Due to this relationship, a good agreement exists also between the MT levels in the healthy kidney studied here and the MT content determined in the Canadians [26].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Such a relationship has been reported earlier for MT levels in human renal cortex or liver and metal content [26]. The metal content of the healthy kidney is within the range of results of earlier reports that estimated the Zn and Cd contents in Canadians [26]and Swedes [27]. Due to this relationship, a good agreement exists also between the MT levels in the healthy kidney studied here and the MT content determined in the Canadians [26].…”
Section: Discussionsupporting
confidence: 71%
“…This is in agreement with the results of Saika et al [28]who found immunohistologically a more intense MT expression in normal renal tubules than in renal cell carcinomas. A same assessment was made for the MT content in malignant and nonmalignant tissues of human liver [25], primary colorectal ACs [27], and liver metastases of colorectal ACs [29]. …”
Section: Discussionmentioning
confidence: 99%